(untitled) (Journal of Computational Mathematics, 2021)
The paper considers the L^∞ convergence for conforming finite elements, such as Argyris element, Bell element and Bogner-Fox-Schmit element, solving the boundary value problem of the biharmonic equation. The nearly optimal order L^∞ estimates are given.